Single-cell microRNA-mRNA co-sequencing reveals non-genetic heterogeneity and mechanisms of microRNA regulation - Nayi Wang (Nature Portfolio, 2019)
Single-cell RNA sequencing allows characterizing cell-to-cell heterogeneity at transcriptome scale. Here, the authors present an approach that enables microRNA and mRNA sequencing in the same single cell, providing insights into the origins of non-genetic cellular variability and mechanisms of miRNA regulation.